Kompetensi pustakawan Universitas Islam Negeri Syarif Hidayatullah Jakarta menghadapi Masyarakat Ekonomi Asean (MEA) - Yusnimar Yusnimar (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This study discusses the competencies of librarians at State Islamic University (UIN) SyarifHidayatullah Jakarta in facing the ASEAN Economic Community (AEC). The purpose of the researchis to analyze the competencies of librarians at UIN Syarif Hidayatullah Jakarta and their readiness toface the competitiveness in the AEC era. This study uses questionnaires for data collection supoortedby observation and interviews. Descriptive analysis is employed for data analysis. The finding of theresearch shown that the librarian of the State Islamic University (UIN) Syarif Hidayatullah havefulfiled the required comptencies but have not been ready to compete in the AEC era so that they needto strengthen their competencies.